2012
DOI: 10.1161/circresaha.112.278705
|View full text |Cite
|
Sign up to set email alerts
|

Red Wine and Cardiovascular Health

Abstract: Downloaded from Circulation ResearchSeptember 28, 2012 resveratrol (≈70%), but several other polyphenols and phenolic acids contribute. 23 Also, both red wine and resveratrol enhance eNOS enzymatic activity. Whereas the effect of resveratrol on eNOS phosphorylation (and activation) mainly involves estrogen receptor-mediated activation of extracellular signalregulated kinases 1 and 2, 24 the phosphorylation (and activation) of eNOS by phenolic extracts from red wine also involves the phosphatidylinositol 3-kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Dietary curcumin, which has an antioxidant effect, can improve aging-related cerebrovascular dysfunction in rodents [110]. Resveratrol, a natural polyphenol in grapes and red wine, has been shown to have beneficial effects on glucose and lipid metabolism, vascular function, and antioxidative properties [111,112]. A Mediterranean diet rich in resveratrol is associated with a significantly reduced risk of cardiovascular diseases [113].…”
Section: Dietary Approaches To Stop Hypertensionmentioning
confidence: 99%
“…Dietary curcumin, which has an antioxidant effect, can improve aging-related cerebrovascular dysfunction in rodents [110]. Resveratrol, a natural polyphenol in grapes and red wine, has been shown to have beneficial effects on glucose and lipid metabolism, vascular function, and antioxidative properties [111,112]. A Mediterranean diet rich in resveratrol is associated with a significantly reduced risk of cardiovascular diseases [113].…”
Section: Dietary Approaches To Stop Hypertensionmentioning
confidence: 99%
“…The cardiovascular protective effects of red wine are widely acknowledged according to the hypothesis of the "Mediterranean diet model" and "French paradox." 1,2 Recent research found that polyphenols such as resveratrol and catechin played the antiatherosclerosis role in red wine. 3 As one of the oldest wines in China, rice wine is brewed from a mixture of aspergillus oryzae, yeast, rice, and water.…”
Section: Introductionmentioning
confidence: 99%
“…As regards cardioprotection, experiments using wine, de-alcoholized wine and spirits, in conditions of moderate intake, point to health benefits deriving from polyphenols and, possibly, other bioactive phytochemicals that may counteract the detrimental effects of ethanol. On the other hand, because of the positive effects of low amounts of alcohol on HDL-cholesterol and haemostatic factors, ethanol and polyphenols may also exert additive and/ or synergistic protective effects on cardiovascular system (Hansel et al, 2012;Li and Förstermann, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 2), possess different molecular and biochemical targets both in healthy and diseased cells (Iriti and Faoro, 2009). Their main mechanisms of (cardio) protection include high antioxidant and antiinflammatory activities; resveratrol, in particular, has been reported to stimulate endothelial production of nitric oxide, reducing oxidative stress, decreasing vascular inflammation and preventing platelet aggregation (Li and Förstermann, 2012). Furthermore, the diversity of grape and wine chemistry has been recently improved by the discovery of new bioactive molecules in these products, i.e.…”
Section: Introductionmentioning
confidence: 99%